(untitled) (Veterinary Science, 2017)
In the present work the importance of electronic microscopy is analyzed as a tool in the study of microorganisms.Besides, an analysis of different working methods on bacteriologic samples is done in transmission microscope preparing a work protocol adjusted to the structural characteristics of the environmental mycobacteria